ANÁLISE VARIACIONISTA DO RÓTICO TEPE NA FALA DE DESCENDENTES DE UCRANIANOS EM PRUDENTÓPOLIS NO PARANÁ - Souza, Daiane Cristina Moreira de (2022)
This research aims to analyze the conditioning factors for the realization of rhotic sounds, the so-called r sounds, especially r tap, in the Portuguese spoken by Ukrainian descendants living in rural communities in the city of Prudentópolis, a municipality located in the southern region of Paraná. The methodology of this research is based on the theory of Variationist Sociolinguistics (LABOV, 2008 [1972]), to investigate speech data, describing the realization of the rhotic sounds and possible favoring factors. The rhotic sounds are quite common in languages and are characterized by multiple variants with different manners and places of articulation. As corpus of the research, sixteen interviews from the VARLINFE database are analyzed, corresponding to spontaneous speech samples from eight male and eight female informants who belong to two age groups, less than 50 years old and more than 50 years old, and have two levels of education - elementary and junior high school. Most of the informants are of Ukrainian ethnicity and only two are of hybrid ethnicity, consisting of a Ukrainian father and a Polish mother. To analyze the rhotic sounds, we first listened to the interviews, noting the excerpts in which the use of the rhotic variants, the object of this study, occurred, totaling 6,506 analyzed data. These occurrences, after being duly coded, were submitted to statistical treatment with the Goldvarb program. The general results show the occurrence of four variants in the informants' speech: the tap, the velar vibrant, the retroflex, and a variant not yet identified, which needs to be acoustically analyzed. The results revealed the predominance of the tap rhotic variant and pointed out as conditioning factors for its realization the syllabic environment in which the sound occurs in the word, the morphological class of the word, the sound context before and after the rhotic in the word, the age group, gender and ethnicity of the speaker. This research contributes to the knowledge and record of Ukrainian ethnic speech in Brazil and of Brazilian Portuguese spoken in the interior of Paraná.